Acalabrutinib monotherapy for treatment of chronic lymphocytic leukaemia (ACE-CL-001): analysis of the Richter transformation cohort of an open-label, single-arm, phase 1–2 study. Issue 12 (December 2021) - Eyre, Toby A; Schuh, Anna; Wierda, William G; Brown, Jennifer R; Ghia, Paolo; Pagel, John M; Furman, Richard R; Cheung, Jean; Hamdy, Ahmed; Izumi, Raquel; Patel, Priti; Wang, Min Hui; et al.
Summary: Background: Patients with chronic lymphocytic leukaemia who progress to Richter transformation (diffuse large B-cell lymphoma morphology) have few therapeutic options. We analysed data from the Richter transformation cohort of a larger, ongoing, phase 1–2, single-arm study evaluating the safety and activity of the selective, irreversible Bruton's tyrosine kinase inhibitor acalabrutinib for the treatment of chronic lymphocytic leukaemia or small lymphocytic lymphoma. Methods: For this open-label, single-arm, phase 1–2 study, patients aged 18 years or older with biopsy-proven treatment-naive or previously treated diffuse large B-cell lymphoma (Richter transformation) or prolymphocytic leukaemia transformation (Eastern Cooperative Oncology Group performance status ≤2) were assigned to receive oral acalabrutinib 200 mg twice daily as monotherapy until disease progression or toxicity. Patients were enrolled across seven centres from four countries. Safety and pharmacokinetics were assessed as primary endpoints; secondary endpoints were overall response rate, duration of response, and progression-free survival. Safety was assessed in the all-treated population (patients who received ≥1 dose), and activity was assessed in the all-treated population (for progression-free survival) and efficacy-evaluable population (for response rate; patients in the all-treated population with ≥1 response assessment after the first dose). This trial is registered with ClinicalTrials.gov (NCT02029443 ). Findings: Between Sept 2, 2014, and April 25, 2016, 25 patients with Richter transformation were enrolled; 12 (48%) were male and 23 (92%) were White. As of data cutoff (March 1, 2021), two (8%) of 25 patients remained on acalabrutinib. The median time on study was 2·6 months (IQR 1·8–8·4). The most common adverse events (all grades) were diarrhoea (12 [48%] of 25 patients), headache (11 [44%]), and anaemia (eight [32%]). The most common grade 3–4 adverse events were neutropenia (seven [28%] of 25) and anaemia (five [20%]). The most common reason for treatment discontinuation was disease progression (17 [68%] of 25 patients). 11 (44%) deaths were reported within 30 days of the last acalabrutinib dose; none was considered treatment-related. Acalabrutinib was rapidly absorbed and eliminated, with similar day 1 and day 8 exposures. The overall response rate was 40·0% (95% CI 21·1–61·3), with two (8%) of 25 patients having a complete response and eight (32%) having a partial response; the median duration of response was 6·2 months (95% CI 0·3–14·8). Median progression-free survival in the overall cohort was 3·2 months (95% CI 1·8–4·0). Interpretation: Acalabrutinib appears to be generally well tolerated, although progression-free survival was relatively poor in this cohort of patients with Richter transformation. On the basis of these findings, the use of acalabrutinib monotherapy in this setting is limited; however, further assessment of acalabrutinib as part of combination-based regimens for patients with Richter transformation is warranted. Funding: Acerta Pharma, a member of the AstraZeneca Group.